2003
DOI: 10.1007/s00464-002-9102-5
|View full text |Cite
|
Sign up to set email alerts
|

Our experience with 250 laparoscopic adjustable silicone gastric bandings

Abstract: Most patients prefer laparoscopy as the surgical technique in the treatment of morbid obesity. Our initial experience with 250 operations confirms that this approach is as good as open surgery. The long learning curve is steep, requiring at least 100 cases to guarantee low complication rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…To minimize the rates of erosions and complications in general, it is recommended in the literature that laparoscopic bands should be inserted by experienced bariatric surgeons because the learning curve is steep, requiring at least 100 cases to guarantee low complication rates [15,[19][20][21]. This is reflected in our series, with 14 BEs (83%) occurring in the initial 300 band patients (incidence, 4.7%) and 3 BEs occurring in the last 565 patients (incidence, 0.53%).…”
Section: Discussionmentioning
confidence: 99%
“…To minimize the rates of erosions and complications in general, it is recommended in the literature that laparoscopic bands should be inserted by experienced bariatric surgeons because the learning curve is steep, requiring at least 100 cases to guarantee low complication rates [15,[19][20][21]. This is reflected in our series, with 14 BEs (83%) occurring in the initial 300 band patients (incidence, 4.7%) and 3 BEs occurring in the last 565 patients (incidence, 0.53%).…”
Section: Discussionmentioning
confidence: 99%
“…A month after surgery, inflation of SAGB was commenced by injecting 3 or 4 ml of a radiology contrast medium (Iopamiro isotonic 200 mg IO; Bracco, Milan, Italy) under aseptic conditions in an out- [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Of the 190 patients who underwent SAGB, 184 (97%) could be followed up (mean, 39.4 ± 18.4 months; duration of follow-up, 6-72 months).…”
Section: Postoperative Follow-upmentioning
confidence: 99%
“…In many studies on LAGB, the percentage of patients in follow‐up is often not reported or is poorly defined18–25. When described, the proportion of patients lost to follow‐up tends to increase with the length of follow‐up.…”
Section: Introductionmentioning
confidence: 99%